Decolonising the commissioning of Indigenous health and wellbeing program evaluations in Australia. (30th September 2020) - Finlay, S; Judd, J; Roe, Y; Fredericks, B; Smith, J; Foley, D; Boulton, A; Cargo, M
Abstract: Background: Significant financial investments have been made to improve the life expectancy gap between Indigenous people and other Australians over the last 10 years. Despite the investment, few evaluations have been commissioned to assess program effectiveness. Indigenous leaders have been calling for a more active role in the commissioning of Indigenous program evaluations. This project aims to identify how government and non-government commissioning practices can better support Indigenous engagement and leadership in the evaluation of health and wellbeing programs in Australia. This presentation reports on the different commissioning models that support Indigenous program evaluations, from the perspectives of commissioners, evaluators and program providers. Methods: Semi-structured interviews were conducted with 20 Indigenous and non-Indigenous commissioners, evaluators and program providers. A mixed coding procedure was used. Interviews were coded using deductively derived codes reflecting best practice principles in Indigenous evaluation and inductively derived codes from participant stories. Interviews were analysed using NVivo qualitative software. A collaborative group-based approach to data analysis was used guided by Indigenous Standpoint Theory. Results: The commissioning of Indigenous-specific program evaluations in Australia reflects top-down, participatory, co-design and Indigenous-led approaches. Top-down approaches were considered 'extractive' and had limited or token Indigenous input. Indigenous models were more strongly aligned with best practice and reflected authentic Indigenous engagement. There was agreement across the stakeholder groups on the value of Indigenous engagement in the commissioning process. The presentation will elaborate on the different approaches, their characteristics, strengths/ limitations. Conclusions: Diverse approaches to commissioning are used and reflect different levels of Indigenous engagement and leadership. Key messages: In the commissioning of Indigenous evaluations there needs to be governance structures to support Indigenous engagement. In the commissioning of Indigenous evaluations there needs to be greater input by Indigenous people.